(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
Each strand of mathematical proficiency requires the development of sometimes overlapping skills. Instead of debating which strand demands the most attention, mathematics educators have been discussing ways in which to adequately develop every strand. Adaptive reasoning is a set of skills that can be difficult to develop and may require teachers to adjust their established teaching practices. If educators have access to successful researched-based instructional strategies, they will be better prepared to develop these skills in their students. There is widespread agreement that students who are unable to adequately reason will have limited mathematical proficiency, and there are several research-based strategies educators can use to develop adaptive reasoning skills in young students of mathematics.